Hubungan Antara Kebiasaan Tidak Sarapan Pagi dan Konsumsi Tablet Tambah Darah terhadap Resiko Kejadian Anemia pada Remaja Putri di SMPN 1 Nibong - Zakia Ulrahmah; Hafni Zahara; Futry Maysura (JURNAL RISET RUMPUN ILMU KESEHATAN, 2026)
Anemia is a micronutrient deficiency problem that is common in various parts of the world. Indonesia is one of the countries with a high anemia rate. According to the 2024 Basic Health Research (Riskesdas), the anemia rate in adolescent girls reached 32%. Breakfast habits and consumption of iron supplements affect daily nutritional intake. Low hemoglobin levels occur due to infrequent iron supplement consumption and inadequate food intake, resulting in a lack of iron stores in the body. The purpose of this study was to encourage adolescent girls to continue maintaining good habits of consuming iron supplements and having a healthy breakfast. This study used a quantitative analytical observational method with a cross-sectional design. The target population was female students of SMPN 1 Nibong. The study was conducted at SMPN 1 Nibong. The sample was obtained using a cluster random sampling technique of 50 respondents. The results of the chi-square test showed a strong association between breakfast habits and the risk of anemia, with a p-value of 0.000, which is far below 0.05, so technically significant. In essence, breakfast habits and blood supplement consumption have been shown to influence the risk of anemia in adolescent girls at SMPN 1 Nibong. The school is expected to promote understanding of nutrition and the importance of breakfast and blood supplement consumption, as well as motivate students to eat breakfast and consume blood supplement tablets regularly.